2022
DOI: 10.1136/ejhpharm-2021-003013
|View full text |Cite
|
Sign up to set email alerts
|

Failure mode and effect analysis applied to improve the medication management process in a pharmacy of a teaching hospital and a proposal for a simplified rating system

Abstract: BackgroundHealthcare is not as safe as it should be and medication error remains a significant source of preventable morbidity and mortality among patients.ObjectivesTo present a failure mode and effect analysis (FMEA) of the medication management process in the pharmacy of the largest teaching hospital in Tunisia. Secondly, to examine the validity of a proposed simplified risk rating method by comparing the degree of concordance with the FMEA rating system in classifying failure modes related to the studied p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…These numbers illustrate a substantial advancement in pharmacy operations, emphasizing a deliberate effort to eliminate inefficiencies and optimize workflow. Even in studies where specific percentages were not provided [ 35 , 68 , 83 ], the recurrence of this theme highlights its significance in today's healthcare landscape. These studies collectively indicated an industry-wide initiative to refine processes, a necessary step for the sustainable provision of healthcare services.…”
Section: Reviewmentioning
confidence: 99%
“…These numbers illustrate a substantial advancement in pharmacy operations, emphasizing a deliberate effort to eliminate inefficiencies and optimize workflow. Even in studies where specific percentages were not provided [ 35 , 68 , 83 ], the recurrence of this theme highlights its significance in today's healthcare landscape. These studies collectively indicated an industry-wide initiative to refine processes, a necessary step for the sustainable provision of healthcare services.…”
Section: Reviewmentioning
confidence: 99%